It' Happened, but Not Again : A Minskian Analysis of Japan's Lost Decade. - Marc-André Pigeon (Levy Economics Institute of Bard College, 2000)
This paper asks two questions. First, can we explain Japan's ongoing financial crisis by means of an institutional analysis similar to the one Hyman P. Minsky applied to the U.S. economy during the postwar period? Second, what are the implications of this analysis for what is going on in the Canadian and U.S. economies today. To answer the first question, we develop an interpretation of Japan's postwar history and particularly the evolution of its financial institutions that we believe fits Minsky's institutional analysis. We begin by identifying three broad periods in Japan's postwar economic history through 1990. We label the 1945 to 1972 period as "stable," thanks in part to tight regulation of the financial and trading system. By the early 1970s and through the end of the decade, however, these systems were under severe strain for both internal and external reasons. Internally, Japan's largest companies were relying less on bank credit to finance investment and trade and more on retained earnings. This affected the financial system by reducing bank profitability and forcing banks to seek business elsewhere, notably in the real estate sector. Externally, Japan suffered from the collapse of the Bretton Woods exchange-rate system, increasing trade tensions with the United States that led to "forced" deregulation, and what were two very difficult oil shocks for a country unusually reliant on oil imports. During the last period, from 1980 to 1990, Japan'seconomy easily outperformed the OECD countries, leading to yet more pressure from abroad to deregulate and stimulate domestic demand. Ultimately, we suggest that the country's financial system was not able to adapt adequately to a rapidly changing domestic and international setting. This created a powder keg for ill-considered fiscal and monetary policy (surpluses and high interest rates) and fertile ground for the financial crisis that took root in 1990 and persists to some extent today. To answer the second question, we draw parallels between events leading up to Japan's 1990 stock market crash and events in the United States and Canada today, with particular emphasis on the current policy stance in both countries toward budget surpluses and inflation. We argue there are good reasons to be concerned that history may be about to repeat itself.
Keywords: 330